2017
DOI: 10.1016/j.blre.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Complementopathies

Abstract: The complement system is an essential part of the innate immune system that requires careful regulation to ensure responses are appropriately directed against harmful pathogens, while preventing collateral damage to normal host cells and tissues. While deficiency in some components of the complement pathway is associated with increased susceptibility to certain infections, it has also become clear that inappropriate activation of complement is an important contributor to human disease. A number of hematologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 100 publications
2
75
0
8
Order By: Relevance
“…Notably, in ex-vivo experiments, when the serum of women with HELLP syndrome and severe preeclampsia are mixed with cells lacking the GPI-anchored proteins CD55 and CD59, increased killing activity is seen compared to serum from healthy controls [75]. The magnitude of this cell killing activity is similar to the effect seen with aHUS serum, which is widely accepted as a complement-mediated disorder [76]. Ex-vivo, eculizumab reduces the killing effect on cells lacking the GPI proteins when serum from subjects with aHUS, HELLP and preeclampsia is used.…”
Section: The Complement System In Stage 2 Of Preeclampsiamentioning
confidence: 99%
“…Notably, in ex-vivo experiments, when the serum of women with HELLP syndrome and severe preeclampsia are mixed with cells lacking the GPI-anchored proteins CD55 and CD59, increased killing activity is seen compared to serum from healthy controls [75]. The magnitude of this cell killing activity is similar to the effect seen with aHUS serum, which is widely accepted as a complement-mediated disorder [76]. Ex-vivo, eculizumab reduces the killing effect on cells lacking the GPI proteins when serum from subjects with aHUS, HELLP and preeclampsia is used.…”
Section: The Complement System In Stage 2 Of Preeclampsiamentioning
confidence: 99%
“…2,9,12 The predominant mechanism of erythrocyte breakdown, known as extravascular hemolysis, is phagocytosis of cells opsonized with complement protein C3b, generated by the classical pathway. 2,[13][14][15] Essential clinical manifestations are anemia and, in up to 90% of the patients, cold-induced acrocyanosis and/or Raynaud phenomena. 10 Although most literature emphasizes the importance of avoiding cold exposure, descriptive studies have shown that 70% to 80% of unselected patients have received pharmacologic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Today, CAD is considered a well‐defined clinico‐pathological entity (Randen et al , ; Berentsen, ; Baines & Brodsky, ; Jaeger, ). It should be distinguished from secondary CA syndrome (CAS), a similar but still more uncommon cold haemolytic syndrome complicating a distinct underlying clinical disease (Berentsen et al , ).…”
mentioning
confidence: 99%